The Inerrancy of the Bible and the History of Salvation in Christianity - Tri Prapto, Suwito; Simanjuntak, Ferry; Belay, Yosep (IJOSMAS, 2022)
It is remarkable that salvation is God's Old Testament for all mankind, since man falls into sin, God lovingly plans salvation. so it is a long historical process of salvation from the Old Testament to the New Testament and its continuation. The fall of man in sin makes his creation separate from God and makes him lose the glory of God. God became a distant God. No man can draw near to Him. In the New Testament, it is said, only by believing in Jesus Christ that man is saved (John 3:16). The concept of redemption of Jesus Christ gives the understanding that by believing in Jesus Christ man is saved. Man cannot survive because of the Law, or because of his own efforts, no one fulfills the Torah completely. In the NT, the road to safety becomes very clear. Jesus proclaimed Himself to be the only way to salvation (John 3:16 & 14:6). And brightly; Jesus said that His coming was not to negate the Torah, but to fulfill it (Matthew 5:17).